Low-Temperature Specific Heats of the beta and zeta Phases in Equiatomic AgZn - Abriata, J. P. (1970)
Fil: Abriata, J. P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina